The Correlation between Apolipoprotein B Level and Inflammatory Markers in Obese - Dian Anindita Lubis; Dharma Lindarto (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2019)
Apolipoprotein B (ApoB) levels reflect the total number potentially atherogenic particles that can predict cardiovascular risk. The purpose of this study was to assess if the ApoB in obese subjects is associated with inflammatory markers. This cross-sectional study was conducted on 80 obese patients at H. Adam Malik Hospital, Medan, Indonesia. Results: Of the 80 patients studied, the average age was 38.95 + 8.13 years old. There was a strong positive correlation between ApoB and triglycerides (r=0.44, p<0.001), low-density lipoprotein cholesterol (r=0.74, p<0.001), and HOMA-IR (r=0.31, p=0.005), however not with the inflammatory markers; adiponectin (r=-0.23, p=0.41) and Chemerin (r=0.021, p=0.851). In obesity, ApoB significantly associated with lipid and insulin resistance, as a risk factor for cardiovascular disease.